Impact of the U.S. Food and Drug Administration's Safety‐Related Announcements on the Use of Bisphosphonates After Hip Fracture. (31st March 2016) - Kim, Seoyoung C; Kim, Dae Hyun; Mogun, Helen; Eddings, Wesley; Polinski, Jennifer M; Franklin, Jessica M; Solomon, Daniel H
ABSTRACT: The U.S. Food and Drug Administration (FDA) issued several announcements related to potential risk of bisphosphonates including osteonecrosis of the jaw (2005), atrial fibrillation (2007), and atypical femur fracture (2010). We aimed to evaluate the impact of three FDA drug safety announcements on the use of bisphosphonates in patients with hip fracture using claims data from a U.S. commercial health plan (2004‐2013). We calculated the proportion of patients in each quarter who received a bisphosphonate or other osteoporosis medication in the 6 months following hospitalization for hip fracture. Segmented logistic regression models examined the time trends. Among 22, 598 patients with hip fracture, use of bisphosphonate decreased from 15% in 2004 to 3% in the last quarter of 2013. Prior to the 2007 announcement, there was a 4% increase in the odds of bisphosphonate use every quarter (OR 1.04; 95% CI, 1.02 to 1.07). After the 2007 announcement, there was a 4% decrease in the odds of bisphosphonate use (OR 0.96; 95% CI, 0.93 to 0.99) every quarter. The announcement in 2007 was associated with a significant decline in the rate of change of bisphosphonate uses over time ( p < 0.001), but no impact on other osteoporosis medication use ( p = 0.2). After the 2010 announcement, the odds of bisphosphonate use continued to decrease by 4% (OR 0.96; 95% CI, 0.94 to 0.98) each quarter and the odds of other osteoporosis medication use remained stable over time (OR 0.99; 95% CI, 0.96 to 1.02). The FDA safety announcement related to atrial fibrillation in 2007 was significantly associated with a decrease in bisphosphonate use among patients with hip fracture. © 2016 American Society for Bone and Mineral Research.